Multi-resolution in architecture as a design driver for additive manufacturing applications. (September 2020) - Ladron de Guevara, Manuel; Borunda, Luis Ricardo; Byrne, Daragh; Krishnamurti, Ramesh
Additive manufacturing is evolving toward more sophisticated territory for architects and designers, mainly through the increased use of scripting tools. Recognizing this, we present a design and fabrication pipeline comprised of a class of techniques for fabrication and methods of design through discrete computational models. These support a process responsive to varied design intents: this structured workflow expands the design and fabrication space of any input shape, without having to explicitly deal with the complexity of discrete models beforehand. We discuss a multi-resolution-based methodology that incorporates discrete computational methods, spatial additive manufacturing with both robotic and commercial three-dimensional printers, as well as, a free-oriented technique. Finally, we explore the impact of computational power on design outcome, examining in-depth the concept of resolution as a design driver.